Apus pacificus ... - Bishop, K. David (Zenodo, 2023)
[FORK-TAILED SWIFT Apus pacificus] Status No previous records of this Palearctic migrant on any of the Teluk Cenderawasih Islands or in virtually all of northern New Guinea (Beehler & Pratt 2016). However, Richardson (1997) noted some sizeable groups of this species passing through in late November 1996, and on 25 August 2008 A. Whitlock saw three near Warafri (eBird checklist 48738894), but neither record is documented. More convincing details were provided by J. Mazenauer (in litt. 2021) from the airport on nearby Numfor. As noted under the previous species, on the evening of 25 September 2018, during a period of strong winds, he saw a group of ten of this species, which he identified by the clear white rump, deeply forked tail and white scaling on the underparts, before they flew east and disappeared. It therefore seems that both this and the previous species pass through the region, at least during autumn passage. ... : Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 29, DOI: 10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130 ...